2007
DOI: 10.1007/s12119-007-9001-y
|View full text |Cite
|
Sign up to set email alerts
|

Premarital Sexual Attitudes and Behavior at a Religiously-Affiliated University: Two Decades of Change

Abstract: Decades of increases in premarital sexual involvement of college students have been related to numerous variables, one of which is religiosity. This investigation sought to determine any change in the premarital sexual attitudes and behaviors of students enrolled at a private religiously-affiliated university over a two-decade period of time. Using anonymous questionnaires administered in social science classes in 1981, 1991, and 2000, a total sample of 1,545 never-married undergraduates, 791 women and 754 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…More religious individuals tend to be more conservative about men’s and women’s roles (Davis and Greenstein 2009), likely due to beliefs that men should be the head of the household and women should be the caregivers. In addition, more religious individuals are less likely to have ever had intercourse and tend to have fewer sexual partners (Earle et al 2007; Lefkowitz et al 2004). Thus, more religious young men may have more conventional attitudes about male role norms, and also limit their number of sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…More religious individuals tend to be more conservative about men’s and women’s roles (Davis and Greenstein 2009), likely due to beliefs that men should be the head of the household and women should be the caregivers. In addition, more religious individuals are less likely to have ever had intercourse and tend to have fewer sexual partners (Earle et al 2007; Lefkowitz et al 2004). Thus, more religious young men may have more conventional attitudes about male role norms, and also limit their number of sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies in the United States, mean age at first sexual intercourse is reported to be 17 years (Earle et al 2007). Almost 90% of men and 85% of women in the United States have had sex before marriage (Siegel et al 1999;Pinkerton et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Harding and Jencks (2003) found that permissive sexual attitudes abruptly increased during the 1960s and 1970s but then remained relatively static in the 1980s and 1990s in nationally representative samples. Earle et al (2007) found that women's sexual attitudes had become more liberal between 1981 and 2000 (in their sample from a religiously-affiliated university). As the editor-in-chief of the journal Sexuality and Culture pointed out to the present authors, current college students are residents of a ''hook-up'' culture which did not exist in previous decades.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Earle et al (2007) studied the sexual attitudes and behaviors of college students at a religiously affiliated university in 1981, 1991, and 2000. The results suggested that, although men remained significantly more permissive in their sexual attitudes than women, over time women had become more accepting of casual sex and sex within the context of a serious relationship.…”
Section: Sexual Attitudesmentioning
confidence: 99%